How presidents answer the call of international capital - Arnold, C; Doyle, D; Wiesehomeier, N (SAGE Publications, 2023)
How do governments manage expectations from international capital keen on pressuring them into adopting market-oriented economic policies during times of crises? Studying executive communication in 267 annual state-of-the-union speeches in 12 Latin American countries between 1980 and 2014 reveals two broad options for strategic position-taking on economic policies. First, when times are dire, presidents not only talk more about the economy and less about social policy, but they also attempt to repurpose other policies as an investment in development. Second, economic turmoil encourages presidents to signal policies, which are appealing to international capital owners. However, while currency crises exert more enduring pressure, the effects of loan crises are more fleeting. Our results are particularly relevant to all who seek to understand how governments use public statements to address pressures from financial markets.